(3TQM (B" (3QhVI GdCacGQ aj Yde Gddjd hGdfgGQ (B"s - (3eMeO Hf GdeNJGQ Hf GdCYeT GdYdhj GdTfbjWi ,CHh YHO Gddgs ((3GdTjN Hf eMeO Hf GdTjN Hf eMeO Hf GdTjN GdeNJGQ Hf CMeO GdeNJGQ Hf GdWGdH eMeO Hf GdeNJGQ Hf GdCYeT s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdReGf hbOQg , hbGd ai cJGHg GdYRjR (B: (3hLYdfG Gddjd hGdfgGQ BjJjf CeG HYO , agPG TQM eajO Sgd GdeYGfi , bQjH ZjQ HYjO s
(3BNQgG (B:s
(3jYfi Cf TQa GdRgQI ai GdOQLI GdSGHYI hGdYTQjf ef GdMhJ , hTQa YWGQO ai GdOQLI GdNGeSI YTQI ef GdSfHdI , hgj GdYPQGA GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdfXe ajgG HGdMeQIs
(3fSNI eUMMI s
(3GSJaJMJ HJQLeI ddeDda efbhdg eeG cJHg SjO YHO Gddg Hf eMeO Hf GdbGVi YHO Gddg GdYdhi s
(3bQf GdfSN (B:s
Keywords: (3Gdadcs